The Influence of Self-Efficacy and Self-Control on Academic Procrastination at North Jakarta State Vocational Schools - Widya Nadya Rostania; Sri Zulaihati; Achmad Fauzi (Reflection: Education and Pedagogical Insights, 2023)
Academic procrastination is influenced by factors such as students’ self-efficacy and self-control. This study aims to find out the impact of students’ self-efficacy and self-control toward academic procrastination. To answer the research objectives, quantitative research with a survey method was applied. The data were collected through questionnaire focused on three variables; self-efficacy, self-control, and academic procrastination. The participants in this study were 105 from two vocational high schools in Jakarta. The data were analyzed by using four kinds of analysis; requirement test, regression equation, hypothesis test, multiple correlations, and coefficient of determination. The results revealed the participants had high scores in academic procrastination with an average score of 57, low self-efficacy with an average score of 94, and low self-control with an average score of 99. Furthermore, the data showed there were negative and significant impacts of both self-efficacy and self-control toward academic procrastination. It implies that the better self-efficacy and self-control of students, the less likely they will procrastinate and vice versa.